Perancangan Sistem E-Reporting Menggunakan ReactJS dan Firebase - Jeremy Panjaitan; Andrew Fernando Pakpahan (Jurnal Teknik Informatika dan Sistem Informasi, 2021)
The head office of west region of Seventh Day Adventist Indonesia in Indonesia is located in Jakarta. Every month employees must report every transaction they have made . The report can be in the form of proof of purchase, shopping receipt, notes and other proof of transactions. The reporting system of the office is done by submitting a hardcopy proof of the transaction to the finance department. The reporting process takes a long time and allows for inaccurate proof of transactions. Another problem that is often found is the unknown status of reports. Employees often do not know whether the reports that have been received by the financial department have been approved or not. The purpose of this study is to design an E-reporting system that will make it easier for employees to report to the financial department so that reporting can be done quickly and accurately. The system to be built uses ReactJS and Firebase using an Agile Software development method. The result of this research is the creation of an E-reporting application that can help to report on the financial department every month.